2018
DOI: 10.3892/or.2018.6700
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between miR‑148a and DNMT1 suppresses cell migration and invasion by reactivating tumor suppressor genes in pancreatic cancer

Abstract: DNA methylation is an epigenetic mechanism that cells use to control gene expression, which serves an important role in tumorigenesis. DNA methyltransferase 1 (DNMT1) is responsible for the maintenance of the pattern of DNA methylation. Overexpression of DNMT1 is observed in numerous malignant tumors, including pancreatic cancer, and results in silencing of several key tumor suppressor genes (TSGs). Recent studies have suggested that microRNAs (miRNAs/miRs) contribute to the regulation of DNMT1 expression, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…DNA methylation is a form of epigenetic modification and an important mechanism of gene expression regulation (3,4). The occurrence and development of tumors are closely related to DNA methylation abnormalities, which are mainly manifested as a decrease in the overall genomic methylation level in tumor cells and an increase in the methylation level of the promoter region of specific genes (5)(6)(7)(8). Previous studies have shown that methylation abnormalities in multiple promoter regions are closely related to the development of pancreatic cancer (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is a form of epigenetic modification and an important mechanism of gene expression regulation (3,4). The occurrence and development of tumors are closely related to DNA methylation abnormalities, which are mainly manifested as a decrease in the overall genomic methylation level in tumor cells and an increase in the methylation level of the promoter region of specific genes (5)(6)(7)(8). Previous studies have shown that methylation abnormalities in multiple promoter regions are closely related to the development of pancreatic cancer (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…As a member of the DNA methyltransferases (DNMTs), DNMT1 plays an important role in mediating gene expression and chromatin structure, by preserving existing DNA methylation during DNA replication (7). DNMT1 was found to be upregulated in various types of cancer, including pancreatic cancer (8). A study of pancreatic cancer demonstrated that lower expression of DNMT1 reversed the resistance to 5-azadeoxycytidine (9).…”
Section: Introductionmentioning
confidence: 99%
“…Many reports suggested that aberrant DNA methylation is involved in the development and progression of pancreatic cancer. Tumor suppressor genes often show hypermethylation of the promoter, thereby suppressing its expression and contributing to the pathogenesis of PDAC [16,17]. Zhou et al [17] found that methylation frequencies of CpG sites within promoter of LITAF were signi cantly higher in PDAC tissues, and LITAF promoter hypermethylation was associated with low LITAF expression.…”
Section: Discussionmentioning
confidence: 99%
“…DNMT1 overexpression was observed in approximately 80% of pancreatic carcinomas [41], where many promoters of key tumor suppressor genes (TSGs) were hypermethylated [42]. Overexpression of DNMT1 was reported to be responsible for silencing key tumor suppressor genes such as p16, PENK, and RASSF1 [43]. Moreover, several studies on PDAC have reported an increase in non-specific and targeted gene-specific 5-hydroxymethylation.…”
Section: Dna Methylationmentioning
confidence: 99%